The Inuit presence at the first Canadian Truth and Reconciliation Commission national event - Gadoua, Marie-Pierre (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2010)
This paper addresses various forms of healing and reconciliation among Canadian Inuit and First Nations, in regards to the Indian residential school system and the Truth and Reconciliation Commission (TRC). Stemming from fieldwork at the TRC’s first national event in Winnipeg (June 2010), I present observations that are supplemented by previous studies on Aboriginal healing methods in Canada. Although Inuit and First Nations healing and reconciliation strategies are based on common themes—tradition and community—in practice they diverge notably, both in their principles and in their applications. First Nations seek healing by activating a sense of community that often transcends their specific cultural group or nation, using pan-Indian spiritual traditions and ceremonies. In contrast, the Inuit most commonly seek to preserve and promote specific Inuit traditions and identity as tools in their healing practices. This divergence could be seen in Inuit and First Nations’ participation in the TRC. The creation of the Inuit sub-commission within the TRC in March 2010, resulting from intense lobbying by Inuit leaders, was a first sign of the group’s distinctive approach to healing. But the unfolding of the TRC’s first national event in Winnipeg showed again how these differences materialise in practice and contribute to a better understanding of Inuit responses to the repercussions of their colonial past and strategies for healing from the legacy of residential schooling.